2020
DOI: 10.1177/2036361320983691
|View full text |Cite
|
Sign up to set email alerts
|

The management of pancreatic metastasis from synovial sarcoma of the soft tissue: A case report

Abstract: Pancreatic metastases are rare, accounting for 2%–3% of pancreatic tumors. The pancreas represents an unusual metastatic site of synovial sarcoma (SS) outside the usual localizations (regional nodes, lung, bone, and liver). The diagnosis is evoked by the personnel medical history of SS and imaging then confirmed by histological examination of the guided pancreatic biopsy. Its therapeutic management is mainly surgical with extensive removal of the lesion. So far only four cases have been reported in the English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…It is less frequent than carcinoma and affects mostly adolescents. Synovial sarcomas are malignant soft tissue tumors of unknown etiology ( 4 , 5 ). These tumors can appear in a variety of sites and are currently considered to result from a mutation in mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is less frequent than carcinoma and affects mostly adolescents. Synovial sarcomas are malignant soft tissue tumors of unknown etiology ( 4 , 5 ). These tumors can appear in a variety of sites and are currently considered to result from a mutation in mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma, colorectal cancer, melanoma, and lung cancer are the most frequent primary malignancies that cause pancreatic metastases; pancreatic metastases from synovial soft tissue sarcoma are extremely uncommon[ 23 - 26 ]. A review of pancreatic metastases of sarcomas other than clear cell sarcoma showed that the primary tumor was located in the lower limbs[ 27 ]. This observation led scientists to hypothesize that a shunt between the lower limbs and the pancreas existed.…”
Section: Metastatic Clear Cell Sarcoma In the Pancreasmentioning
confidence: 99%